P109 The effect of pleural fluid on survival in patients with a malignant pleural effusion. (12th November 2019) - Sreejith, N; Mercer, R; Lu, Q; Shepherd, G; Addala, D; Castro, O; Vartharajah, R; Thayanandan, A; Hassan, M; Bedawi, E; Asciak, R; Tsikrika, M; et al.
Abstract : Background: Malignant pleural effusions (MPEs) are a sign of advanced malignant disease associated with high mortality and poor clinical outcome. Management of MPEs focuses on achieving symptomatic and radiological control of pleural fluid. Recent in vitro evidence has implicated the presence of even small volumes of pleural fluid in mesothelioma progression. 1 This analysis investigated whether the presence of pleural fluid is associated with poorer survival in all MPE. Methods: A review of all patients diagnosed with MPE between 2015–2017 was performed. Patients were grouped as either having achieved fluid control or not from initial radiological diagnosis until death. Kaplan Meier and Cox regression analysis was performed to assess the effect of a) achieving fluid control and b) duration of fluid, on patient survival. Results: Analysis of the first 100 patients in our data set included 20 mesotheliomas, 27 breast, 4 gynaecological, 8 GI, 31 lung and 10 other cancers. 27 patients achieved fluid control before death and 70 did not. The group with fluid control comprised of those with IPC removal (3), successful pleurodesis (18) and resolution without pleurodesis (6), whereas the group without fluid control included those with ongoing IPC drainage (21), stable without intervention (2) and no resolution (47) at death. Three had no radiology after the initial aspiration and were thus excluded. Fluid control was associated with greater survival in Kaplan Meier survival curve analysis (p=0.009). Similarly, the Cox regression analysis demonstrated that successful control is associated with survival (p<0.001). However, patients who were exposed to pleural fluid for a longer duration had an increased survival (p<0.001). Conclusion: Our findings suggest an association between pleural fluid control and greater survival. However, a statistically significant association was also found between time exposed to pleural fluid and greater survival. We cannot exclude the possibility of unknown confounders, and time dependant analysis may demonstrate different results. Further investigations with similar subgroups such as 'ongoing IPC drainage vs. IPC removal' may prove useful, and further analysis are ongoing. Reference: Cheah HM, et al . Respirology 2017;22:192–199.